Danske kalkmalerier. Senromansk tid 1175-1275. Redaktører Ulla Haastrup og Robert Egevang. Nationalmuseet. (Christian Ejlers Forlag, 1987). 216 s., 348 kr. - Munk-Jørgensen, Wivan (Historie/Jyske Samlinger, 1991)
-